Caffeine Intake and its Effect on Hydration Status Among Workers: A Literature Review - Rosemiarti, Tria; Basrowi , Ray W. (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Introduction: caffeine is one of a compound that is widely found in coffee, tea, energy drink, and chocolate. Their consumption is high among adults, especially workers during working hours. The diuretic effect from caffeine, caffeinated beverages’ density, and drink behavior change due to the consumption of caffeinated beverages might alter the hydration status. Moreover, low hydration status is associated with work performance where heat strain may worsen it. The objective of this study is to review the original studies on the association of caffeine intake and hydration status among workers. Methods: studies were obtained from 4 electronic databases which are Scopus, PubMed, EBSCO, and google scholar. Inclusion criteria were published in English or Bahasa Indonesia, between January 2000 and February 2023. Only originals studies included with the method of experimental or observational studies.Results: there were eighteen studies found regarding the association between caffeine intake and hydration status. The indicator of hydration status varied from urine specific gravity, urine or serum osmolality, urine color, glomerular filtration rate, urine pH, urine volume, body water, and rehydration capability. Most of the intervention was caffeine intake, but two studies involved tea consumption instead. Conclusions: Recent studies suggested inconclusive results between caffeine intake and hydration status in adults where some studies showed insignificant change between intervention and control groups and some others showed the poor quality of hydration status among caffeine consumers. More studies are necessary to conduct, especially among workers since their specifically high consumption of caffeine and the risky environment of working.